RANCANG BANGUN APLIKASI ABSENSI SISWA BERBASIS RFID - Andri Firmansyah; Hasan Bishri (Jurnal SIGMA, 2019)
The application of attendance that occurs in schools is generally still manual in the form of handwriting and absences that require time because inputting into Microsoft Excel, in Microsoft Excel does not provide a student database, where the system causes several problems that occur, besides that in the world of education, especially at SMPIT Thariq Bin Ziyad school, services are very influential on the vision and mission in providing the best service. RFID-based absence is an alternative for writers in overcoming this problem with the VB.Net 2015 interface design and MySQL database integration using the Waterfall method. With the development in the student attendance process and it has been integrated using an RFID card that can be used as a student ID card. This application can help speed up the process of attendance and attendance recapitulation so that it helps the work of various parties to be easier and faster. Keywords: Attendance, RFID, Education, VB.Net 2015, MySQL, Waterfall